Transnational policy flows in European education : the making and governing of knowledge in the education policy field - Nordin, Andreas [Herausgeber]; Sundberg, Daniel [Herausgeber] (Symposium Books, 2014)
"International comparisons of educational achievements have come to play a crucial role in understanding the educational field today. This book provides an in-depth analysis of the development of international large-scale assessments. The lives and achievements of transnational educational experts who paved the way for these assessments are discussed as well as the rise of institutions specialising in the making and managing of educational statistics such as the International Association for the Evaluation of Educational Achievements (IEA) and the Programme for International Student Assessment (PISA) supported by the Organisation for Economic Cooperation and Development (OECD). Emerging transnational policy spaces and their effect on national education policy are also problematised using the concept of 'Europeanisation' as a theoretical reference. By bringing together historical and contemporary comparisons using different methodological approaches the goal of this book is to contribute to a widened understanding of educational policy-making as an open-ended and complex process that cannot be reduced to a rational process of linear implementation, or a deduction of world models of education. Instead the result of this book shows that transnational policy flows in many directions in European education today and is being negotiated, translated, interpreted or even contested when recontextualised in different national and/or local arenas." (Publisher, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; I 2.2 Europa; EU-Bildungspolitik; Europäische Integration; Europäischer Bildungsraum; Leistungsbewertung; Kompetenzfeststellung; Bildungsreform; Bildungssteuerung; Europa